Systematic analysis of A-to-I RNA editing upon release of ADAR from the nucleolus - Ruben Lattuca; Rümeyza Bascetin; Vincent Detours; Denis L. J. Lafontaine (RNA Biology)
Adenosine-to-inosine (A-to-I) RNA editing, catalysed by two ADAR isoforms (p110 and p150) and ADARB1, is a critical regulatory step in gene expression. Intriguingly, the nucleolus is conspicuously rich in ADAR p110 and ADARB1, though the biological reason remains unclear. To investigate a putative role of nucleolar enrichment in ADAR, we released it gradually from the nucleolus into the nucleoplasm by treating cells briefly with low doses of actinomycin D, known to disassemble the nucleolus. Deep sequencing of the transcriptome revealed that as ADAR dissociated from the nucleolus, RNA editing increased significantly, with sharp rises in both the number of edited sites and editing frequency. This co-transcriptional editing, predominantly in intronic regions, was associated with disrupted pre-mRNA splicing, causing exon skipping and intron retention which remodelled gene expression. These findings suggest that the nucleolar localization of ADAR serves to restrain its activity, preventing excessive editing that could lead to splicing errors and cellular dysfunction.